AB0597 Adaptation of Ucla Scleroderma Clinical Trial Consortium Gastrointestinal Tract 2.0 Questionnaire into Turkish. (15th July 2016) - Tas, M.Y.; Keskinoglu, P.; Kenar, G.; Yarkan Tugsal, H.; Zengin, B.; Dervis Hakim, G.; Can, G.; Onen, F.; Akkoc, N.; Akarsu, M.; Birlik, M.A.
Abstract : Background: Nearly 90% of patients with scleroderma (SSc) have gastrointestinal tract (GIT) involvement in variable severities and is a challenging process for clinicians. The University of California Scleroderma Clinical Trial Consortium Gastrointestinal Tract 2.0 (UCLA SCTC GIT 2.0) is a questionnaire including 34 items, 7 multi-item scales: reflux, distention/bloating, diarrhea, fecal soilage, constipation, emotional well-being and social functioning. By these parameters, a total GIT score is calculated (1). This scale translated in German, Italian, French, Polish, Spanish, Swedish, Dutch before, they are available in http://www.uclascleroderma.researchcore.org/ website (1–3). There is no Turkish version of this scale yet. Objectives: Our aim is to make translation, cultural adaptation of the UCLA SCTC GIT 2.0 into Turkish, and assess reliability of the scale in patients speaking Turkish. Methods: UCLA SCTC GIT 2.0 scale was translated into Turkish according to international guidelines and applied to 97 SSc patients. The questionnaire repeated in 29 patients after an interval of 15 days for determining reliability. For internal consistency, Cronbach's alpha was calculated, reliability coefficient if item deleted and test-retest reliability also determined. External consistency was measured by comparing with the Short Form (SF)-36 by Spearman's correlation analysis (rho: ≤0.29 weak, 0.30–0.49 middle, ≥0.50 strong). Results: 97 scleroderma patients were included in this study (female:87.6%, mean age:55.4±11.4). Internal consistency Cronbach's alpha was calculated as 0.89, reliability coefficient if item deleted was 0.89–0.90. External consistency of UCLA SCTC GIT 2.0 was measured by comparing with the SF-36, correlation was meaningful in medium level (Table 1, 2 ). Conclusions: UCLA SCTC GIT 2.0 scale had strong internal consistency, good reliability and acceptable validity when adapted into Turkish. Turkish-speaking patients with scleroderma, this scale will be useful to assess GIT symptoms. The basic constraint of our study was, not using image procedures for objective GIT involvement evidences. References: Khanna D, Reliability and validity of the UCLA SCTC GIT Instrument.Arthritis Rheum, 2009. Bae S, Development and validation of French version of the UCLA SCTC GIT Instrument.Clin Exp Rheumatol, 2011. Meijs J, Translation, cross-cultural adaptation, and validation of the UCLA SCTC GIT 2.0 into Dutch. Clin Exp Rheumatol, 2014. Disclosure of Interest: None declared